PROBLEMATIKA PELAKSANAAN PERSIDANGAN PERKARA PERCERAIAN PADA MASA PANDEMI COVID-19 DI PENGADILAN AGAMA KELAS 1A MAKASSAR TAHUN 2020-2021 - Andi Titah Niagara Unga Putri; Lomba Sultan; Hadi Daeng Mapuna (Universitas Islam Negeri Alauddin Makassar, 2022)
The main problem in this study is about the Problems of Implementing Divorce Trials During the Covid-19 Pandemic in the Makassar Class 1A Religious Court in 2020-2021. This study aims to determine the implementation of the Divorce Trial at the Makassar Class 1A Religious Court during the Covid-19 Pandemic; Knowing the Effect of Covid-19 on the Process of Implementing Divorce Trials at the Makassar Class 1A Religious Court. This type of research is field research. While the data collection uses primary data and secondary data. The data analysis used is qualitative data analysis and the research approach used in this thesis is empirical juridical, namely research that is carried out directly in the field to find out the real problems that occur, then will be linked to the applicable laws and regulations and existing legal theory. . The results of the study show that: 1) The implementation of the divorce case trial is basically the same as before the Covid-19 pandemic, only the difference lies in the technical process where the process can be done online and offline. The use of the electronic system itself is in the form of E-Court, Elitigation and Teleconference. 2) The influence that was felt by the Makassar Class 1A Religious Court during the Covid-19 pandemic, of course, there were some such as the work system, which used to be full time in the office but after Covid-19 a work from home system was implemented, but it didn't last long because there are several things that are considered less effective from this WFH system. In the trial itself, the effect is if the trial was carried out manually, but after the Covid-19 pandemic the trial could be carried out technologically, and this is certainly not optimal because other users, namely people who still do not understand the use of technology, besides that the trial implementation It can be said that it is relatively closed because access to electronically participate in the trial is only intended for litigants and is not yet open to be accessed by the public. The implications of this research are, 1) It is hoped that in the future human resources and supporting tools for case administration services in courts electronically will be more prepared to face developments in the world of justice. 2) It is necessary to apply regulations regarding the administration of cases in courts electronically and more effectively, then it is necessary to carry out a thorough socialization of court service users. 3) To improve convenience for people seeking justice, it is also necessary to improve services that are more leverage so that it is easier for the public to access goods manually or online. Keywords: Divorce, Trial, Covid-19 Pandemic